The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1002/jemt.10175
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐induced pathways in breast cancer

Abstract: Hypoxia, a common consequence of solid tumor growth in breast cancer and other cancers, serves to propagate a cascade of molecular pathways which include angiogenesis, glycolysis, and alterations in microenvironmental pH. Hypoxia-inducible factors, heterodimeric DNA binding complexes composed of two subunits, provide critical regulation of this response. This review presents a synopsis of the genes induced by hypoxia in the context of breast cancer and discusses how upregulation of HIF-1 activity, and the homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 101 publications
1
48
0
1
Order By: Relevance
“…Antiangiogenesis therapy has shown that hypoxic regions can survive and repopulate the tumor after therapy (Yu et al, 2002). Hypoxic tumor cells are also more resistant to chemotherapy primarily due to the lack of an efficient way to deliver the drugs to these cells (Giatromanolaki and Harris, 2001;Koukourakis, 2001;Goonewardene et al, 2002). Radiation that relies on the formation of ROS to induce apoptosis is also ineffective in hypoxic cells due to the low rate of oxidative phosphorylation (Koukourakis, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Antiangiogenesis therapy has shown that hypoxic regions can survive and repopulate the tumor after therapy (Yu et al, 2002). Hypoxic tumor cells are also more resistant to chemotherapy primarily due to the lack of an efficient way to deliver the drugs to these cells (Giatromanolaki and Harris, 2001;Koukourakis, 2001;Goonewardene et al, 2002). Radiation that relies on the formation of ROS to induce apoptosis is also ineffective in hypoxic cells due to the low rate of oxidative phosphorylation (Koukourakis, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, tumor cells can adapt to hypoxic conditions by employing a variety of survival tools, which result in the promotion of cancer cell growth and metastasis. [1][2][3] This adaptation of cancer cells to hypoxia is mainly mediated by the transcription factor hypoxia-inducible factor-1 (HIF-1). 4 HIF-1 is a heterodimeric transcription factor consisting of an oxygen-regulated a subunit (HIF1a) and a stable nuclear factor, HIF-1b/aryl hydrocarbon receptor nuclear translocator (ARNT).…”
mentioning
confidence: 99%
“…3,4 Early premalignant breast cancer lesions, including ductal carcinoma in situ (DCIS), often display increased expression of hypoxic markers, including the oxygen-labile a subunit of hypoxiainducible factor (HIF)-1 and exhibit poor architectural and cellular differentiation. 5 Indeed, HIF-1α expression occurs at low levels in normal breast tissue and ductal hyperplasias but is elevated in the majority of DCIS and invasive lesions.…”
Section: Surviving Without Oxygenmentioning
confidence: 99%